PERCEPTIONS ABOUT ACCEPTABILITY OF ONLINE DEGREES IN HIRING OR PROMOTION DECISIONS IN TECHNOLOGY SERVICES INDUSTRY IN INDIA - Saini, Nitin (Digital Repository of Theses - SSBM Geneva, 2023)
Today’s economies are based on education and knowledge. The newer technologies and internet dissemination has not only led to the demand for skilled talent in India’s technology services industry outpacing the supply of the skilled talent but also led to popularizing of online education. The COVID pandemic further pushed the education providers to move towards online education thereby increasing the availability of online degree holders to the industry. With boom in EdTechs, India has become the second largest market for e-learning, and the number of online degree holders are increasing at the rapid pace, but the question is whether supply of online degree holders from online education providers will be able to meet the demand for skilled talent in technology services in India. The current research study was an attempt to investigate the acceptability of degrees earned online (partially or fully) by prospective technology employers in India for hiring and promotion decisions, using Mixed Methods Methodology. The theoretical framework of equivalency theory was used to come up with and to conduct the online web-based questionnaire survey and the detailed interviews of selected few. The findings indicate that while online education is becoming popular, the employers of technology industry in India do have a bias towards traditional degrees compared to online degrees for hiring and promotions decisions. Certain organizational policies may contribute towards such bias and influence the employer’s decision during hiring and promotion. The online degrees were found to be more acceptable at later stages of career than at the beginning stage of the career, and it varies with the type of vii position. The experience, skills and level of education were found to be more influential during the later stages of career than the mode of education. Additionally, the small-sized and mid-sized companies were found to be more open to accept online degrees. The greatest stigma associated with online education was found to be the lack of interpersonal skills and interactions with other students and faculties. This stigma can possibly be nullified by taking up activities like internships, apprenticeships, blogging, and networking. The contribution of this study is relevant to students, online education providers and employers.